Effects of Metformin on TSH Levels and Benign Nodular Goiter Volume in Patients Without Insulin Resistance or Iodine Insufficiency - dos Santos, Patricia Borges; Gertrudes, Larissa Nascimento; Conceição, Flavia Lucia; de Andrade, Bruno Moulin; Carvalho, Denise Pires de; Vaisman, Mario; Teixeira, Patricia de Fatima dos Santos (Frontiers in Endocrinology, 2019)
Objectives: To evaluate the impact of metformin (MTF) use on TSH levels, thyroid volume and volume of benign thyroid nodules (TNs). Additionally, to study if iodine status influences the outcomes. Methods: A total of 23 euthyroid patients (42 TNs) with benign thyroid nodules, diagnosed by fine needle aspiration biopsy, were randomly assigned to MTF or placebo (P) use for six months. Serum TSH, homeostatic model assessment for insulin resistance (HOMA-IR), and urinary iodine concentrations (UIC) were assessed. Ultrasound was used to evaluate TNs and thyroid volumes (TV) and their variations throughout the study. Diabetic patients, those undergoing levothyroxine replacement, and/or using thyroid- or insulin level-influencing drugs were excluded. Results: The sample consisted predominantly of patients without IR. Both intervention groups were similar regarding several confounding variables and showed a comparable median UIC. Serum TSH decreased significantly after MTF (-0.21 vs 0.09 mUI/L in the P group; p=0.015). At six months, no significant variations were found between groups with respect to TN volumes, TV, HOMA-IR, or body mass index (BMI). However, a tendency toward enlargement of TV with placebo (16.0%; p=0.09) and a protective effect of MTF on growing TN (OR: 0.25; CI 0.05–1.20) was detected after excluding patients with IR (a lower UIC subgroup). The reduction on TSH levels with MTF maintained in the population without iodine insufficiency (-0.24 vs +0.07 in the P group; p=0.046) and was accentuated in those with excessive or more than adequate UIC (-0.69; p=0.043). A protective effect of MTF on growing TN was suggested (OR:0.11; IC:0.02-0.84) in those with higher UIC. Conclusions: This study demonstrated that MTF caused a reduction in TSH levels in benign nodular goiter. This effect was more accentuated in patients with higher levels of UIC and was accompanied by a suggested protective effect on TN enlargement.